Strategi Pengamanan Akses Jaringan Dengan L2TP Over IP Security Pre-shared Key Dan Port Knocking - Rianda Pratama (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
The rapid development of technology affects people's lifestyles in various lines. Various kinds of data exchange occur through the internet causing the internet to become a basic need for most people. Therefore, the Government sees the need for a system that accommodates these needs through Presidential Regulation number 95 of 2018 concerning an electronic-based government system. In its implementation, one of the things needed is the management of access to data stored on government servers. In order to support the needs of government server managers, a technology that can accommodate security needs in accessing the server is needed, the authors design this access through a Virtual private server Layer 2 Tunneling Protocol Over IP Security and port knocking which allows managers who have access rights to access the network. locally via the public internet network securely.